Posyandu dalam era transformasi integrasi layanan primer dan intervensinya - Kusrini, Agatha Ratri Rini; Natalio, Rahmat; Sinaga, Evi Susanti (JOURNAL of Public Health Concerns, 2025)
Background: Lifecycle-based health services are a strategic approach to primary care transformation in Indonesia, positioning the Integrated Health Post (Posyandu) as a crucial community-based service. However, the implementation of Posyandu still faces various obstacles, such as a lack of trained cadres, suboptimal health education, and limited educational facilities and media, particularly in reaching target groups. Purpose: To evaluate the implementation of integrated Posyandu and to increase the capacity of cadres through outreach and the development of educational media. Method: This community service activity was conducted in Kebon Baru Village in January 2025. Eight participants participated. The first stage involved identifying Posyandus based on the lifecycle, encompassing a systems approach, evaluating input, process, and output aspects, and observing the service process directly at the Posyandu. The second stage involved providing education and developing educational media to enhance cadre knowledge and facilitate knowledge transformation. Results: Data obtained showed that the level of knowledge of cadres before the outreach activity was categorized as good (4%, 50%) and poor (4%, 50%). Meanwhile, the level of knowledge after being given extension activities was in the good category as many as 7 (87.5%) and in the less category as many as 1 (12.5%). Conclusion: Integrated health post (Posyandu) activities have implemented life cycle or integrated services, which, based on the identification results, are actively running and have been awarded the "Purnama Posyandu" status. Community service activities, including providing counseling and creating educational media, have helped improve cadre knowledge and optimize their role in providing education to the community at the Posyandu and during home visits. Suggestion: Training is recommended for each cadre to ensure equitable knowledge and skills, so that life cycle-based Posyandus will provide increasingly optimal services, particularly health services, to the community. Keywords: Counseling; Health cadres; Integration of primary services; Integrated Service Post Pendahuluan: Pelayanan kesehatan berbasis siklus hidup merupakan pendekatan strategis dalam transformasi layanan primer di Indonesia, yang menempatkan Posyandu sebagai layanan berbasis masyarakat yang penting. Namun, pelaksanaan Posyandu masih menghadapi berbagai kendala, seperti kurangnya kader terlatih, belum optimalnya edukasi kesehatan, serta keterbatasan sarana dan media edukasi, terutama dalam menjangkau kelompok sasaran. Tujuan: Untuk mengevaluasi pelaksanaan posyandu terintegrasi dan meningkatkan kapasitas kader melalui penyuluhan serta pengembangan media edukasi. Metode: Pengabdian masyarakat ini dilaksanakan di Kelurahan Kebon Baru pada bulan Januari 2025. Kegiatan ini diikuti oleh 8 peserta. Pada tahapan pertama melakukan identifikasi posyandu berdasarkan siklus hidup meliputi pendekatan sistem yakni mengevaluasi dari aspek input, proses, dan output serta kegiatan observasi dengan memantau secara langsung proses pelayanan di Posyandu. Selanjutnya untuk tahapan kedua adalah memberikan edukasi dan pembuatan media edukasi untuk meningkatkan pengetahuan kader dalam melakukan transformasi pengetahuan. Hasil: Mendapatkan data bahwa tingkat pengetahuan kader sebelum diberikan kegiatan penyuluhan yang dalam kategori baik sebanyak 4 (50.0%) dan kategori kurang sebanyak 4 (50.0%). Sedangkan tingkat pengetahuan setelah diberikan kegiatan penyuluhan yang dalam kategori baik sebanyak 7 (87.5%) dan dalam kategori kurang 1 (12.5%). Simpulan: Kegiatan posyandu sudah menjalankan layanan siklus hidup atau terintegrasi yang berdasarkan hasil identifikasi sudah berjalan aktif dan telah mendapat strata posyandu purnama. Kegiatan pengabdian masyarakat melalui pemberian penyuluhan dan pembuatan media edukasi telah membantu meningkatkan pengetahuan kader dan mengoptimalkan peran kader dalam memberikan edukasi kepada masyarakat di posyandu maupun saat kunjungan rumah. Saran: Diharapkan untuk memberikan pelatihan kepada setiap kader sebagai upaya kesetaraan pengetahuan dan ketrampilan sehingga posyandu berbasis siklus hidup akan memberikan pelayanan yang semakin optimal khususnya pelayanan kesehatan kepada masyarakat.